Implementation of Occupational Safety and Health Standards in Government Offices in the Province of Negros Occidental, Philippines - Cagbaleño, Leslie Rose; Palic, Anabelle S. (Technium Social Sciences Journal, 2025)
Occupational Safety and Health Standards (OSHS) are crucial for ensuring the well-being of workers and was underscored by the United Nations 2030 Agenda for Sustainable Development. While previous research examined OSHS in various settings, studies on the public sector have been rarely explored. Despite the issuance of OSHS guidelines for government, policy and practices needs further investigation and action. This descriptive-comparative study, which utilized a researcher-made survey questionnaire based on CSC-DOH-DOLE JMC No. 1 s 2020, aimed to assessed the implementation of OSHS across three levels of governance (national, provincial and city) within a highly urbanized city. It analyzed how the extent of implementation varies across these levels focusing on the areas of workplace safety, emergency preparedness, occupational safety and health programs, support facilities, working hours, breaks and leave privileges, and working environment. The respondents were the 340 permanent employees who have worked for at least three years and were selected through stratified random sampling. The employee profiles were analyzed using descriptive analysis, while mean, standard deviation, frequency count, and percentage distribution were utilized to analyze the responses and their variability. The implementation differences across the three levels were examined through comparative analysis. The results of the study showed that employees generally assessed the extent of implementation of the OSHS as great across all governance levels. The national government offices showed significant difference from both the provincial and the city government offices. On the areas of the OSHS, comparison showed that the national level is the lowest in the implementation of occupational safety and health programs while highest in the working hours break and leave privileges. Both the provincial and city level are lowest in the implementation of support facilities. The provincial level showed highest implementation of working hours break and leave privileges while the city level is highest in emergency preparedness and workplace safety. An action plan was proposed to enhance the OSHS implementation of government offices.